Sixth Five Year Plan 1980-85 Some Relevant Facts Uttar Pradesh - Planning Commission (Planning Commission, 1980)
Sixth Five-Year Plan—Outlays and expenditure, Sixth Five-Year Plan—Minimum Needs Programme Financial progress, Sixth Five-Year Plan—Main physical targets and achievements, Sixth Five-Year Plan—Summary statement of centrally sponsored schemes, Weights and index of growth of different industries in Uttar Pradesh, Comparative growth rates in Uttar Pradesh and India, Power shortage in Uttar Pradesh, Creation and utilisation of irrigation potential in Uttar Pradesh, Central and State Governments borrowings, Market borrowings, Uttar Pradesh vis-a-vis All-India, Some facts relating to Uttar Pradesh, Economic indicators—Inter-State data.
Government of Uttar Pradesh, Planning Department